Power quality in future electrical power systems - Zobaa, Ahmed F.; Abdel Aleem, Shady H. E. (IET energy engineering series ;, 2017)
This book shows how to maintain reliable, continuous, secure and predictable supply in the electrical power network. It deals with challenges such as the penetration of large-scale renewable energy generation, the advances in nonlinear loads, and increased electricity demands in the deregulated market. In addition, the book covers recent requirements for smart grids, highlighting the need for better hierarchical design with enhanced quality, improved controllability, higher reliability, and security. The book also includes novel research linking the past, present and future of electrical power grids from a power quality perspective.